Using Soma Cubes to Master Common Core State Standards - Mickus, Amanda (Ohio Journal of School Mathematics, 2017)
The Soma cube is a three-dimensional puzzle constructed using seven different three-dimensional puzzle pieces. Despite the heavy mathematics foundation of the Soma cube, the puzzle has been utilized in a wide variety of spaces such as entertainment, psychological research studies, and both elementary and secondary classrooms. This article outlines specific classroom applications in elementary, middle, and high school. Research supporting the classroom activities and specific Common Core State Standards addressed by those applications are included.